Scoping Review: The Trajectory of Recovery of Participation Outcomes following Stroke - Batya Engel-Yeger; Tamara Tse; Naomi Josman; Carolyn Baum; Leeanne M. Carey (Behavioural Neurology)
Participation is a central concept in health and well-being and healthcare, yet operationalizing this concept has been difficult. Its definition, uses in healthcare, and impacts on recovery require ongoing research. Our review question goes like this: from the longitudinal evidence investigating participation among stroke survivors, what are the patterns of participation recovery in stroke survivors over time, and what interventions are used to improve participation? To fully understand these questions, we also ask, how is participation defined in the stroke literature, and what are the measures of participation used in the stroke literature? A systematic scoping review was undertaken using the search terms “stroke,” “longitudinal,” “participation,” and “outcome” in seven databases. Articles included were published until April 2017, written in English, and had at least two longitudinal assessments of participation. Fifty-nine articles met the inclusion criteria. The International Classification of Functioning, Disability and Health was the most frequent definition of participation used (34%). There were 22 different measures of participation. Eight of ten studies demonstrated significant improvements in participation up to 12 months poststroke. Efficacy of interventions and their impact on participation varied. The various definitions, measures, and intervention efficacies of participation highlight the need for further research worldwide into achieving meaningful participation and quality of life among stroke survivors. Future practice should include participation as a main outcome measure.